Global ant biodiversity and biogeography – A new database and its possibilities - Majer, Jonathan; Dunn, Robert; Sanders, M. J. (2007)
Despite several centuries of research, the global patterns of species diversity, individual abundance and community composition and their drivers and subtleties remain poorly resolved. We have developed a global database for the di-versity of ants, perhaps the best-studied of ecologically important insect taxa. We describe the database and aspects of its limitations and, at more length, possibilities. The database offers the possibility of testing general macroecological theory with an ecologically important group of insects. The database will also allow us to understand ways in which the global diversity, distribution and biogeography of ants differs from the more often studied vertebrates and plants and some of the consequences of those differences.